Efimov effect in D spatial dimensions in AAB systems - Rosa, D. S. [UNESP]; Frederico, T.; Krein, G. [UNESP]; Yamashita, M. T. [UNESP] (American Physical Society (APS), 2018)
The existence of the Efimov effect is drastically affected by the dimensionality of the space in which the system is embedded. The effective spatial dimension containing an atomic cloud can be continuously modified by compressing it in one or two directions. In the present Rapid Communication we determine the dimensionality D for which the Efimov effect can exist for different values of the mass ratio A=mB/mA for a general AAB system formed by two identical bosons A and a third particle B in the two-body unitary limit. In addition, we provide a prediction for the Efimov discrete scaling factor exp(π/s) as a function of a wide range of values of A and D, which can be tested in experiments that can be realized with currently available technology.
Keywords: Atomic clouds; Efimov effects; Identical bosons; Rapid communication; Scaling factors; Spatial dimension; Two directions; Unitary limits